Down-regulation of catalase activity contributes to senescence induction in wheat leaves exposed to shading stress - Causin, Humberto Fabio; Marchetti, Cintia Florencia; Pena, Liliana Beatriz; Gallego, Susana Mabel; Barneix, Atilio Jose (Springer, 2018)
In shaded wheat (Triticum aestivum L.) leaves, the suppression of blue radiation (BR) triggers senescence. This phenomenon is correlated to an increase in oxidative stress symptoms and a decrease of catalase (CAT) activity, among other traits. Previous data suggest that the radiation signal transduction pathway may involve changes in Ca2+ and H2O2 homeostasis. For better a understanding of the interaction among the spectral composition of radiation, Ca2+ availability, and the antioxidant metabolism in the regulation of shade-induced senescence, detached wheat leaves were placed in a growth chamber and exposed to either blue (B, high BR transmittance) and/or green (G, very low BR transmittance) Lee® filters in the absence or presence of 0.8 mM verapamil (a Ca2+ channels blocker), 4.0 mM EGTA (a Ca2+chelator), or 8.0 mM 3-amino-1,2,4-triazole (a CAT inhibitor). At defined time points, the leaf samples were analyzed for changes in chlorophyll content, specific activities of CAT, ascorbate peroxidase (APX), and guaiacol peroxidase (POX), CAT isozymes, and gene expression of CAT1, CAT2, and two senescence markers (TaSAG1 and TaSAG3). BR transmittance decreased the chlorophyll degradation rate and SAG genes expression either in leaves continuously exposed under the B filter, as well as in leaves previously exposed under the G filter. The effect of BR was associated with the maintenance of a high CAT (but not APX and POX) activity, and it was suppressed either in the presence of 3-AT or when Ca2+ availability was decreased. BR altered the CAT activity both at the transcriptional and at the posttranscriptional level. Nevertheless, different responses of CAT isozymes and CAT genes expression profiles to specific treatment combinations indicate that they differed in their regulatory pathways.